2003
DOI: 10.9749/jin.108.129
|View full text |Cite
|
Sign up to set email alerts
|

Evacuation Experiments for Wheelchair User and Pedestrian Group

Abstract: Disabled people including wheelchair users have been going out into a society rnore actively , Then TRAIL ( Transportation and Accessibility Law )carne into effect in May 2000 . Barrier − free passenger ships are going on increas 至 ng by those activities . Barrier − free passenger ships must maintain highly evacuation safety on board . One of items for evacuation safety on board{ s that wheelchair users and pedestrian passengers can move together to assembl } 厂 spaces smoothly . We did experiments that a wheel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There are also studies that have paid attention to the movement of pedestrians mixed with wheelchair users recently. Feliciani et al [23] found that information on exits provided to wheelchair users can increase the evacuation efficiency in a room with Type: electrically and Wheelchair users: [24] manually self-propelled fixed speed; and assisted wheelchair normal people: users; number: 1 kindness, competitiveness Tsuchiya et al Japan 1.2, 1.4, Type: assisted Normal walking [25] 1.6, 1.7, wheelchair users; 1.8, 2.0 number: 0-3 Shimada and Japan 3 Type: self-propelled Normal walking Naoi [26] and assisted wheelchair users; number: 0-4 Geoerg et al Germany 0.9, 1.0, Type: assisted Normal walking [18] 1.1, 1.2 wheelchair users (with disability); number: 7 The author (more China 2.1 Type: assisted Normal walking details in section 2) wheelchair users; number: 6 four exits. With respect to the corridor scenarios, the experimental setup and conditions of the corresponding studies are summarized in table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also studies that have paid attention to the movement of pedestrians mixed with wheelchair users recently. Feliciani et al [23] found that information on exits provided to wheelchair users can increase the evacuation efficiency in a room with Type: electrically and Wheelchair users: [24] manually self-propelled fixed speed; and assisted wheelchair normal people: users; number: 1 kindness, competitiveness Tsuchiya et al Japan 1.2, 1.4, Type: assisted Normal walking [25] 1.6, 1.7, wheelchair users; 1.8, 2.0 number: 0-3 Shimada and Japan 3 Type: self-propelled Normal walking Naoi [26] and assisted wheelchair users; number: 0-4 Geoerg et al Germany 0.9, 1.0, Type: assisted Normal walking [18] 1.1, 1.2 wheelchair users (with disability); number: 7 The author (more China 2.1 Type: assisted Normal walking details in section 2) wheelchair users; number: 6 four exits. With respect to the corridor scenarios, the experimental setup and conditions of the corresponding studies are summarized in table 1.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the corridor scenarios, the experimental setup and conditions of the corresponding studies are summarized in table 1. A slower speed of pedestrians overtaking wheelchair users with the assisted type compared to the self-propelled type of wheelchair is observed from a corridor experiment conducted by Miyazaki et al [24]. Concentrating on assisted wheelchair users, some studies have investigated their movement characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Wright et al (1999) evaluated walking speed of 30 individuals with visual impairments through an egress route. Miyazaki et al (2003) carried out a series of experiments using 30 participants and one participant with a wheelchair to describe the behavior of individuals encountering an individual using a wheelchair in a corridor with variable widths. Daamen and Hoogendoorn (2011) conducted an experiment to investigate the capacity of doorways with consideration of the elderly and people with disabilities in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%